2017
DOI: 10.3847/2041-8213/aa9d86
|View full text |Cite
|
Sign up to set email alerts
|

Nova Ophiuchus 2017 as a Probe of 13C Nucleosynthesis and Carbon Monoxide Formation and Destruction in Classical Novae

Abstract: We present a series of near-infrared spectra of Nova Ophiuchus 2017 in the K band that record the evolution of the first overtone CO emission in unprecedented detail. Starting from 11.7days after maximum, when CO is first detected at great strength, the spectra track the CO emission to +25.6days by which time it is found to have rapidly declined in strength by almost a factor of ∼35. The cause for the rapid destruction of CO is examined in the framework of different mechanisms for CO destruction, namely, an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We have estimated the CO mass in SN 2020oi using the LTE model developed by Das et al (2009), which assumes optically thin emission and a pure 12 C 16 O composition. Earlier applications of the model include SN 2017eaw (Rho et al 2018a), SN 2016adj (Banerjee et al 2018), and several novae (Banerjee et al 2016;Joshi et al 2017). We adopted a straight continuum (for the dust emission) passing through the two minima (2.01-2.08 μm and 2.155-2.17 μm) in the spectrum between 2.00 and 2.23 μm.…”
Section: Co and Dust Formation In Type Ic Sn 2020oimentioning
confidence: 99%
“…We have estimated the CO mass in SN 2020oi using the LTE model developed by Das et al (2009), which assumes optically thin emission and a pure 12 C 16 O composition. Earlier applications of the model include SN 2017eaw (Rho et al 2018a), SN 2016adj (Banerjee et al 2018), and several novae (Banerjee et al 2016;Joshi et al 2017). We adopted a straight continuum (for the dust emission) passing through the two minima (2.01-2.08 μm and 2.155-2.17 μm) in the spectrum between 2.00 and 2.23 μm.…”
Section: Co and Dust Formation In Type Ic Sn 2020oimentioning
confidence: 99%
“…We have estimated the CO mass in SN2020oi using the LTE model developed by Das et al (2009), which assumes optically thin emission and a pure 12 C 16 O composition. Earlier applications of the model include SN2017eaw (Rho et al 2018a), SN2016adj (Banerjee et al 2018) and several novae (Banerjee et al 2016;Joshi et al 2017). The best fit model, shown in Figure 8, was determined by varying the CO mass, temperature, and velocity dispersion using chi-square minimization over the region 2.27 to 2.44 µm.…”
Section: Optical and Near-ir Spectroscopy Of Sn Ic And Ic-blmentioning
confidence: 99%
“…For the observational data from Joshi et al (2017), our models show that CO WDs with a mass 1.0-1.1 M or a 1.1 M ONe WDs can approach the narrow 12 C/ 13 C mass ratio observed in this nova. The results are consistent with the spectrographic data in the UV band which also suggested that the observed WD has a mass of 1.0-1.1 M (Miko lajewska & Shara 2017).…”
Section: Production Of Stable Isotopesmentioning
confidence: 77%
“…Their ratio represents how the proton capture competes with the CNO cycle. Another tight measurement from Nova Oph 2017 is given in Joshi et al (2017) which also shows a very low 12 C/ 13 C ratio of 1.6±0.3. In Figure 9 we show the three ratios of our models as a function of WD progenitor mass in comparison to these measurements.…”
Section: Production Of Stable Isotopesmentioning
confidence: 94%